2018
DOI: 10.1098/rsos.172318
|View full text |Cite
|
Sign up to set email alerts
|

Growth profiling, kinetics and substrate utilization of low-cost dairy waste for production of β-cryptoxanthin by Kocuria marina DAGII

Abstract: The dairy industry produces enormous amount of cheese whey containing the major milk nutrients, but this remains unutilized all over the globe. The present study investigates the production of β-cryptoxanthin (β-CRX) by Kocuria marina DAGII using cheese whey as substrate. Response surface methodology (RSM) and an artificial neural network (ANN) approach were implemented to obtain the maximum β-CRX yield. Significant factors, i.e. yeast extract, peptone, cheese whey and initial pH, were the input variables in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…A logistic kinetic model that stimulates growth was suggested by Mitra and Dutta 47 and was adopted to determine the biomass growth ( R. oryzae ) in this study. According to Ajala et al ., 48 the model is characterized by the biomass growth inhibition, independent of substrate and product, which is a common phenomenon encountered in batch culture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A logistic kinetic model that stimulates growth was suggested by Mitra and Dutta 47 and was adopted to determine the biomass growth ( R. oryzae ) in this study. According to Ajala et al ., 48 the model is characterized by the biomass growth inhibition, independent of substrate and product, which is a common phenomenon encountered in batch culture.…”
Section: Methodsmentioning
confidence: 99%
“…The equation shows that the rate of product formation is directly and linearly proportional to growth rate and instantaneous biomass concentration 47 . However, integrating Eqn (9) using the appropriate boundary conditions is represented as Eqn (10): 0PdP= 0ΔttΔtdXdtdt+βtrue 0ΔttΔtXdtAccording to Mitra and Dutta, 47 the term ‘Δ t ’ represented delay in the LA production with respect to biomass growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microorganism Kocuria marina DAGII was isolated from soil during routine screening of pigment producing microorganisms in the department of Biotechnology, NIT Durgapur [11]. This bacteria produces β-cryptoxanthin (β-CRX).…”
Section: Microorganism Cultivation Medium and Pigment Extractionmentioning
confidence: 99%
“…(Venugopalan et al, 2013) showed a significant ability to produce canthaxanthin (CX) as their secondary metabolite. CX is an orange-red ketocarotenoid with significant applications in food and feed industry owing to its strong antioxidant property and anticancer, anti-inflammatory and immunomodulatory activities (Mitra et al, 2018). D. maris NITD is a gram-positive, aerobic, non-motile bacterium that has been established as an efficient CX producer (Goswami et al, 2012).…”
Section: Introductionmentioning
confidence: 99%